PENGARUH MODEL PEMBELAJARAN LEARNING TOURNAMENT TEHADAP HASIL BELAJAR PPKn SISWA KELAS VII SMPN 3 XIII KOTO KAMPAR - Asriatul Rahma; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low student learning outcomes of PPKn at SMPN 3 XIII Koto kampar. The formulation of the problem in this study is